2015
DOI: 10.4172/2155-6105.1000219
|View full text |Cite
|
Sign up to set email alerts
|

The Process of Adapting the Evidence-Based Treatment for Tobacco Dependence for Smokers of Lower Socioeconomic Status

Abstract: Introduction Tobacco use is the leading cause of preventable death and disease and contributes significantly to socioeconomic health disparities. The prevalence of smoking among individuals of lower socioeconomic status (SES) in the US, many of whom are African American (AA), is three to four times greater than the prevalence of smoking among individuals of higher SES. The disparity in tobacco dependence treatment outcomes between lower and higher SES smokers contributes to tobacco-related health disparities a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…None of the studies provided explicit reflections on how relevant these cultural and structural factors are for intervention mechanisms and how they may interact with intervention mechanisms to affect implementation and outcomes in a new context. Other, less commonly mentioned reasons for adaptation included the need to ensure intervention attractiveness [ 40 ], reach [ 45 ], and salience [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…None of the studies provided explicit reflections on how relevant these cultural and structural factors are for intervention mechanisms and how they may interact with intervention mechanisms to affect implementation and outcomes in a new context. Other, less commonly mentioned reasons for adaptation included the need to ensure intervention attractiveness [ 40 ], reach [ 45 ], and salience [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Only six studies reported using existing guidance to inform their adaptation process (see Table 3 ). Nonetheless, most of the studies describing intervention adaptation (and not an evaluation) reported a structured process consisting of sequential phases and steps or key principles [ 27 , 28 , 30 36 , 38 , 39 , 41 , 43 , 45 , 48 ]. Four studies that did not report a phased process, still described well-demarcated procedures [ 24 26 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Adaptation Refinement: Incorporate feedback from Step 3 into the final treatment manual (Barrera and Castro, 2006; Lau, 2006). See Evans et al (2015) for details.…”
Section: Methodsmentioning
confidence: 99%
“…Careful, systematic adaptation of standard, individualized CBT for tobacco dependence for lower SES and/or African American or Black smokers improves short-term failure rates for these groups (Sheffer et al, 2017; Webb Hooper et al, 2017). Sheffer et al (2017) adapted six sessions of standard CBT for lower SES smokers, most of whom identified as Black, using the Barrera and Castro systematic approach for adapting evidence-based behavioral treatments (Barrera and Castro, 2006; Evans et al, 2015). Perspectives from African American and Black smokers were then incorporated using the PEN-3 Model (Airhihenbuwa, 1990, 1992).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation